2016
DOI: 10.1016/j.envres.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal polybrominated diphenyl ether and perfluoroalkyl substance exposures and executive function in school-age children

Abstract: Executive function is a critical behavioral trait rarely studied in relation to potential neurotoxicants. Prenatal exposure to polybrominated diphenyl ethers (PBDEs) and perfluoroalkyl substances (PFASs) has been associated with adverse neurodevelopment, but there is limited research on executive function. Data from 256 mother-child pairs in the Health Outcomes and Measures of the Environment Study, a prospective birth cohort (2003-2006, Cincinnati, OH), was used to examine maternal serum PBDEs and PFASs and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 61 publications
5
69
0
Order By: Relevance
“…While prior epidemiologic studies have not examined prenatal and childhood PBDEs and their relation with visual spatial abilities, two studies have reported sexually dimorphic associations between PBDE exposure and other neurodevelopmental outcomes, with conflicting conclusions. Poorer behavior regulation was observed with increased prenatal BDE-153 concentrations in males, but not in females in this same cohort (Vuong et al, 2016). However, executive function deficits were noted among females with higher postnatal PBDEs in the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) cohort (Sagiv et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…While prior epidemiologic studies have not examined prenatal and childhood PBDEs and their relation with visual spatial abilities, two studies have reported sexually dimorphic associations between PBDE exposure and other neurodevelopmental outcomes, with conflicting conclusions. Poorer behavior regulation was observed with increased prenatal BDE-153 concentrations in males, but not in females in this same cohort (Vuong et al, 2016). However, executive function deficits were noted among females with higher postnatal PBDEs in the Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) cohort (Sagiv et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
“…Prenatal and childhood PBDE exposure have been associated with decrements in cognitive function, impairments in executive function, increased attention deficit/hyperactivity disorder (ADHD) related behaviors and symptoms, and poorer motor coordination in children (Chao et al, 2011; Chen et al, 2014a; Eskenazi et al, 2013; Gascon et al, 2011; Herbstman et al, 2010; Hoffman et al, 2012; Roze et al, 2009; Sagiv et al, 2015; Shy et al, 2011; Vuong et al, 2016). The mechanism by which PBDEs exert their neurotoxic effects is unclear, but suspected mechanisms include disrupting thyroid hormone function (Costa and Giordano, 2007; Kodavanti et al, 2010; Szabo et al, 2009), altering the cholinergic systems (Dufault et al, 2005; Eriksson et al, 2002; Viberg et al, 2003a), causing oxidative stress (Belles et al, 2010; Cheng et al, 2009; Giordano et al, 2008; He et al, 2008), inducing cell apoptosis (Chen et al, 2014b; He et al, 2008; He et al, 2009b), impacting DNA methylation (Woods et al, 2012), and affecting neuronal proteins (e.g., CaMKII, GAP-43, synaptophysin, and tau) and N-methyl-d-aspartate (NMDA) receptors (Buratovic et al, 2014; Viberg et al, 2003b; Viberg et al, 2008; Yan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Exposures to these chemicals induce neurobehavioral effects, indicating adverse effects on the central nervous system (Lau et al 2004, Mariussen andFonnum 2006). For example, in a study by Vuong et al (2016) in school-age children, maternal serum PFOS levels were associated with poorer behavior regulation, metacognition, and global executive functioning. The authors suggested that prenatal exposures to PFOS may be associated with executive function deficits observed in school-age children.…”
Section: Perfluorinated Compoundsmentioning
confidence: 99%
“…Evidence from several epidemiological studies indicates that PBDEs are neurotoxic when exposure occurs during fetal development, with reports of decrements in Full Scale IQ (FSIQ), impaired executive function, lower reading and language abilities, and increased attention deficit/hyperactivity disorder (ADHD) related behaviors (Chen et al, 2014; Cowell et al, 2015; Ding et al, 2015; Eskenazi et al, 2013; Herbstman et al, 2010; Shy et al, 2011; Vuong et al, 2016; Zhang et al, 2016). Postulated mechanisms by which PBDEs may exert neurotoxic effects include indirectly affecting brain development through thyroid hormone disruption or directly acting on brain cells by causing oxidative stress, interfering with signal transduction, altering cholinergic system responses, inducing neuronal apoptosis, and altering neurotransmitter release and function (Costa et al, 2014; Costa and Giordano, 2011; Dingemans et al, 2011).…”
Section: Introductionmentioning
confidence: 99%